The therapeutic potential of mesenchymal stem cells in COVID-19: Present and future - Mutiara Indah Sari; Imam Budi Putra; Dadik Wahyu Wijaya (Belgorod National Research University, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) was first reported in 2019 and has since become a health concern due to its rapid spread and high mortality rate. With the discovery of vaccines, there has been a reduction in disease occurrence, transmission, mortality, and morbidity in a population. However, with the emergence of newvariants, the available vaccines show varying efficiencies depending on the population and variants, while the present drugs may lose their effectiveness, hence the urgent need to explore effective therapies. Mesenchymal stemcells (MSCs) have been widely studied for their anti-inflammatory and immunomodulatory effects as COVID-19treatment and shown their potential to improve the condition of COVID-19 patients. This systematic review aims to assess the therapeutic potential of MSCs as anti-inflammatory and immunomodulatory agent in COVID-19. Materials and Methods: A literature search is performed on PubMed, ScienceDirect, ProQuest, and Google Scholar and potentially relevant studies to review, based on the inclusion and exclusion criteria we have determined.We identified 14,090 publications from our search and excluded duplicates as well as irrelevant studies from title,abstract, and full-text screening. Data extraction and analysis were then performed in the 20 eligible studies. Results and Discussion: Results show that MSCs improve immune system dysregulation throughimmunomodulatory and anti-inflammatory effects, through reducing blood C-reactive protein (CRP) and IL-6 levels. Conclusion: We conclude that MSC is one of the promising treatments in COVID-19 regardless of variants.